DESIGN AND IMPLEMENTATION OF CONTROL AND ACTUATOR SUBSYSTEMS IN PRECISION HYROPONIC NUTRIENT MANAGEMENT SYSTEM - Fauzan Muzakki, Ahmad
Each plant has different characteristics that cause the nutritional needs of each plant is not the same. In the hydroponic plant business, a factor that can be controlled by humans is nutrition given to hydroponic plants. Providing optimal nutrition can increase production results from hydroponic plants. But if the plants lack or have excess nutrients, then the plants will find it difficult to provide optimal yields. This happens because nutrition acts as an ingredient in making energy needed by plants and maintaining balance in plants. In practice, practitioners of hydroponic plants use fertilizer as a nutrient enhancer for plants with the estimation method. This causes the nutrients provided to plants through fertilizer may not be appropriate and can cause losses such as many plants do not grow well or even plants will die, resulting in reduced profits for hydroponic practitioners. Besides hydroponic practitioners sometimes forget to give fertilizer regularly. The solution needed is a product that is able to optimize the nutritional parameters of hydroponics automatically so that the nutrients provided to hydroponic plants can be controlled and are in the optimal range. The product consists of hardware and software in which there is an actuator subsystem as a nutrient controller given to hydroponic plants and a control subsystem as a behavior controller for the actuator subsystem. The product is analyzed and realized to be able to solve problems with the capstone design method. The solution has been implemented and successfully optimized the nutritional parameters of hydroponics automatically.